A family of mixed-lanthanide metal–organic framework thermometers in a wide temperature range. Issue 38 (13th September 2018) - Yang, Yang; Huang, Haipeng; Wang, Yingzhe; Qiu, Fangzhou; Feng, Yan; Song, Xuerui; Tang, Xiaoliang; Zhang, Guolin; Liu, Weisheng
Abstract : By choosing 2-pyridin-4-yl-4, 5-imidazoledicarboxylic acid (H3 PIDC) as the first ligand and sodium oxalate (OX) as the ancillary ligand, a series of mixed-lanthanide metal–organic frameworks (M′LnMOFs) [Tb1− x Eu x (HPIDC)(ox)1/2 H2 O]·3H2 O ( x = 01, 0.012a, 0.032b, 0.052c, 0.082d, 0.12e, 0.32f, 0.52g, 13 ) have been successfully synthesized via hydrothermal reactions. Abstract : By choosing 2-pyridin-4-yl-4, 5-imidazoledicarboxylic acid (H3 PIDC) as the first ligand and sodium oxalate (OX) as the ancillary ligand, a series of mixed-lanthanide metal–organic frameworks (M′LnMOFs) [Tb1− x Eu x (HPIDC)(ox)1/2 H2 O]·3H2 O ( x = 01, 0.012a, 0.032b, 0.052c, 0.082d, 0.12e, 0.32f, 0.52g, 13 ) have been successfully synthesized via hydrothermal reactions.2a–2f can serve as ratiometric luminescent sensors for detecting temperature. In this co-doped system, 2d shows an excellent linear response relationship with temperature from 303 to 473 K and exhibits a maximum relative sensitivity ( S r ) of 0.60% K −1 at 473 K. Furthermore, powder X-ray diffraction (PXRD) experiments indicate that2d has excellent chemical stability under simulated physiological conditions and alkali-acid solutions with pH ranging from 4 to 11, which makes it suitable to be applied in the physiological environment.